HTML5 Multimedia Development Cookbook By Dale Cruse, Lee Jordan - Cruse, Dale (Packt Publishing, 2011)
Written in a cookbook style, this book offers solutions using a recipe based approach. Each recipe contains step-by-step instructions followed by an analysis of what was done in each task and other useful information. Web developers who value the need to stay ahead of the game. This cookbook will give you the edge with practical recipes for wielding this new technology immediately.